A Study on Particle Size Effect of Polyurethane-Mica Composites - Aysel Ersoy; Fatih Atalar; Huseyin Recai Hiziroglu (IEEE Access, 2024)
Nano-sized particles have a significant impact on the dielectric and mechanical properties of polyurethanes. In order to characterize its effects on solid insulators, different types of nanoparticles have been investigated in polymeric materials. One of the filler materials is nanometric mica in the polymer base. Therefore, the objective of this study is to investigate the dielectric properties of mica-filled thermoplastic polyurethane (TPU). Nanometer- and micrometer-size mica fillers with various mixing ratios were doped into TPU. The changes in such dielectric properties as relative permittivity, loss factor, dc conductivity, and breakdown strength have been evaluated in thermoplastic polyurethane composites filled with mica fillers of particle sizes 1 nm, 10 nm, and $5 ~μ \text{m}$ . Physical changes have been observed through Scanning Electron Microscopy (SEM) analysis after adding nano-sized mica particles, while the addition of micron-sized mica particles resulted in samples with breakdown voltages at least 2.5 times higher than pure TPU. The loss factor of the composite, on the other hand, has been found to be the lowest with 3% mica content for 1 nm particle size, 2 % mica content for 10 nm particle size and 1 % mica content for $5 ~μ \text{m}$ particle size.